Peak to Average Power Ratio Reduction of OFDM Signals Using Clipping and Iterative Processing Methods - Hassan, Ahmed K. (Al-Khwarizmi Engineering Journal, 2019)
One of the serious problems in any wireless communication system using multi carrier modulation technique like Orthogonal Frequency Division Multiplexing (OFDM) is its Peak to Average Power Ratio (PAPR).It limits the transmission power due to the limitation of dynamic range of Analog to Digital Converter and Digital to Analog Converter (ADC/DAC) and power amplifiers at the transmitter, which in turn sets the limit over maximum achievable rate. This issue is especially important for mobile terminals to sustain longer battery life time. Therefore reducing PAPR can be regarded as an important issue to realize efficient and affordable mobile communication services. This paper presents an efficient PAPR reduction method for OFDM signal. This method is based on clipping and iterative processing. Iterative processing is performed to limit PAPR in time domain but the subtraction process of the peak that over PAPR threshold with the original signal is done in frequency domain, not in time like usual clipping technique. The results of this method is capable of reducing the PAPR significantly with minimum bit error rate (BER) degradation.